Graphene Nanosheets: Printed Strain Sensors Using Graphene Nanosheets Prepared by Water‐Assisted Liquid Phase Exfoliation (Adv. Mater. Interfaces 9/2019). Issue 9 (9th May 2019) - Manna, Kausik; Wang, Long; Loh, Kenneth J.; Chiang, Wei‐Hung
Abstract : Graphene nanosheets with enhanced exfoliation yield, solution stability and low defects are synthesized by liquid phase exfoliation of graphite in water/N‐methylpyrrolidinone solvents. The as‐fabricate paper‐based strain sensors exhibit high electrical conductivity, low noise floor, and stable electromechanical response. These results pave way for future practical developments and applications of these nanocomposites as strain sensors for structural health monitoring. More details can be found in article number1900034 by Kausik Manna, Long Wang, Kenneth J. Loh, and Wei‐Hung Chiang.